Controlled Synthesis of Organic Nanophotonic Materials with Specific Structures and Compositions. (29th April 2014) - Cui, Qiu Hong; Zhao, Yong Sheng; Yao, Jiannian
<x xml:space="preserve">Abstract</x> Organic nanomaterials have drawn great interest for their potential applications in high‐speed miniaturized photonic integration due to their high photoluminescence quantum efficiency, structural processability, ultrafast photoresponse, and excellent property engineering. Based on the rational design on morphological and componential levels, a series of organic nanomaterials have been controllably synthesized in recent years, and their excitonic/photonic behaviors has been fine‐tuned to steer the light flow for specific optical applications. This review presents a comprehensive summary of recent breakthroughs in the controlled synthesis of organic nanomaterials with specific structures and compositions, whose tunable photonic properties would provide a novel platform for multifunctional applications. First, we give a general overview of the tailored construction of novel nanostructures with various photonic properties. Then, we summarize the design and controllable synthesis of composite materials for the modulation of their functionalities. Subsequently, special emphasis is put on the fabrication of complex nanostructures towards wide applications in isolated photonic devices. We conclude with our personal viewpoints on the development directions in the novel design and controllable construction of organic nanomaterials for future applications in highly integrated photonic devices and chips.